Re-suturing of puerperal perineal wound: An assessment of indications, risk factors and outcomes. (August 2020) - Rotem, Reut; Sela, Hen Y.; Reichman, Orna; Weintraub, Adi Y.; Grisaru-Granovsky, Sorina; Rottenstreich, Misgav
Highlights: Early puerperal perineal wound re-suturing is of rare occurrence, yet, carries potentially short term consequences. Cephalic malposition and meconium stained amniotic fluid were found to be independently associated with puerperal perineal wound re-suturing. Puerperal perineal wound re-suturing is indicated mainly in cases of vulvovaginal hematoma and associated with higher rates of postpartum hemorrhage, blood transfusions, puerperal fever, and longer hospitalizations. Abstract: Objective: To assess the frequency of puerperal perineal wound re-suturing, and to evaluate the indications, risk factors and outcomes of this procedure. Study design: A retrospective series of all parturients that underwent puerperal perineal tear suturing between 2005 and 2019 was undertaken. All parturients who required re-suturing during the delivery hospitalization were identified and compared with those who had puerperal perineal wound repair and did not require re-suturing. General demographics, obstetrical history, current delivery characteristics, re-suturing indications, and outcome were obtained and analyzed. Results: During the study period, 54, 934 parturients required puerperal perineal tear suturing, of which 47 (0.09%) required re-suturing within their postpartum hospitalization. Median time from delivery to perineal re-suturing was 5.38 h [IQR 4.07–7.14]. The most common indication was vulvovaginal hematoma ( n  = 37, 78.7%). The independent risk factors found to be associated with re-suturing were: cephalic malposition (aOR 9.3, 95% CI 1.26–67.74) and meconium stained amniotic fluid (aOR 2.1, 95% CI 1.10–3.85). Parturients who underwent re-suturing had significantly higher rates of postpartum hemorrhage (78.5% vs. 11.4%) blood transfusions (36.2% vs. 1.3%), puerperal fever, and longer hospitalizations ( P  < 0.01 for all). Conclusion: In our population, early re-suturing of puerperal perineal tears is rare, however, it is associated with increased short term maternal morbidity.